Penerapan Language Game Bentuk Permainan Tradisional Sebagai Strategi Pembelajaran Bahasa Arab di Madrasah - Mahfud Saiful Ansori; Ahmad Bashori (Excelencia: Journal of Islamic Education & Management, 2024)
Innovation in Arabic language learning strategies is increasingly developing along with technological developments. This research aims to analyze the effectiveness of implementing traditional language games in Arabic language learning, as well as various factors that support or hinder their implementation. This research uses a quantitative approach with an experimental questionnaire research type using pretest and posttest, as a data collection technique, the T test technique for analyzing data. The research results obtained are based on the t-test carried out by the researcher, the t-test data obtained is 0.4415 which is greater than 0.05, so H0 is accepted, so it can be concluded that there is no difference in Arabic language scores between students who study Arabic with strategies. language game learning with those who don't